(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Cyber security is generally a conservatory of the conventional information system security that is aimed at protecting cyber threats, like cyber terrorism, cyber warfare, and cyber espionage to corrupt digital information. This leads to increase the researches in cyber security. This paper proposes the application of dual watermarking in cyber technology, focusing on forgery detection. The rest of the paper presents a brief overview of cyber security and the role of digital dual watermarking.